Dementia health needs assessment for Cardiff and Vale University Health Board, Wales: a qualitative study. (November 2017) - Beynon, Claire
Abstract: Background: In Cardiff and the Vale of Glamorgan, Wales, an estimated 5000 people have dementia, 58% of whom have a diagnosis. Owing to a growing and ageing population this number is expected to rise to nearly 7000 by 2025. Dementia is the leading cause of death in Wales for women. A health needs assessment is a systematic method to review health issues leading to agreed priorities that improve health and reduce inequalities. The five steps are scoping, identifying health priorities, identifying priorities for change, communicating, and monitoring. The health needs assessment included a review of the literature, review of quantitative data, and a qualitative study. Here I describe the qualitative study. Methods: Interviews were done with 27 carers, staff, and stakeholders; and a focus group of people with dementia was undertaken. Participants were identified with a snowball technique. A list of questions was agreed by a steering group to uncover unmet health needs. This list was used as a guide in all interviews and the focus group, all of which were audio recorded. A thematic review of the interviews and focus group was undertaken. Findings: Data saturation was reached before completion of the interviews. Nine themes were identified from the data: isolation and loneliness (transport was an issue, with most people with dementia unable to drive); kindness and compassion (paid staff need further training); coordination of services (needs further attention); caring for carers (has a direct impact on quality of life for people with dementia who have carers); what to do in a crisis (information and timely support is needed); primary care (where support should be offered); inequity in access (was describe); dementia is everyone's business (the society and environment we live in are important); and prevention (there is limited knowledge of the six steps to reduce the risk of dementia). Interpretation: Inequity in access to services was apparent and needs addressing. Education on risk factors for dementia is needed. A focus on increasing diagnosis rates to ensure that people are offered medication, support, and care is necessary. Carers need timely support, specifically at times of crisis. The study has limited generalisability. Funding: None.